PERAN PROFITABILITAS DALAM HUBUNGAN GOOD CORPORATE GOVERNANCE DAN EFISIENSI BIAYA TERHADAP ISLAMIC SOCIAL REPORTING - Puji Nurhayati; Desy Nur Pratiwi; Erma Wulan Sari; Adelia Rahma Shabira (ITB AAS INDONESIA Surakarta, 2022)
Financial institutions have a very important role in the country's economic efforts. Banking growth in Indonesia is very rapid, based on statistical data on banking improvement until January 2019 as many as 1,922 banking units. The Islamic banking industry in Indonesia is experiencing very strong growth with the potential of Islamic financial assets of 99 billion, making Indonesia ranked 4th in the world in 2020. The existence of CSR disclosure obligations in the company makes the company not only apply the concept of single-buttom-line oriented to achieving maximum profit but the company should pay attention to the triple-buttom-line which includes the financial aspects of the company, social life and the environment. This concept is very linear if implemented in the ISR concept. This study aims to test the influence of Good Corporate Governance (GCG) and cost efficiency on Islamic Social Reporting (ISR) and test the role of profitability in moderating good corporate governance (GCG) and cost efficiency relations on Islamic social reporting (ISR). The study used a sample of 13 companies during 2014-2020. The sampling method in this study used the purposive sampling method. The data analysis techniques used in this study consisted of descriptive statistics, classical assumption tests (normality tests, heteroskedasticity tests, multicollinearity tests, and autocorrelation tests), multiple linear regression analysis tests, partial tests (t) and Moderation Regression Analysis (MRA) tests. The results showed that Good Corporate Governance (GCG) and cost efficiency have an effect and significance on Islamic Social Reporting (ISR). While profitability is not able to moderate the good relationship of Good Corporate Governance (GCG) and cost efficiency to Islamic Social Reporting (ISR). Keywords : Islamic Social Reporting (ISR), Good Corporate Governance (GCG), Cost Efficiency, Profitability, Sharia Bank